ANTESEDEN MINAT BELI KONSUMEN DI SHOPEE - Isnanda Zainur Rohman (Jurnal Ekonomi Dan Bisnis, 2023)
Technological developments have an impact on the convenience of shopping which can be done online and is considered more time saving. One of the marketplaces for conducting online shopping activities is Shopee. This study was conducted to determine the effect of online customer reviews, online customer ratings, product photos, seller service quality, and price discounts on buying interest in the Shopee marketplace. This type of research is quantitative with a sample of 201 people of Yogyakarta who have Shopee. The source of the data used is primary data using a questionnaire. The data analysis method used is multiple linear regression analysis. Based on the results of the study, it was concluded that there was a positive and significant influence on online customer review variables, online customer ratings, product photos, seller service quality, and price discounts on buying interest in the Shopee marketplace.